2021
DOI: 10.1186/s12913-021-07272-9
|View full text |Cite
|
Sign up to set email alerts
|

Out of pocket costs and time/productivity losses for pediatric sepsis in Uganda: a mixed-methods study

Abstract: Background Sepsis disproportionately affects children from socioeconomically disadvantaged families in low-resource settings, where care seeking may consume scarce family resources and lead to financial hardships. Those financial hardships may, in turn, contribute to late presentation or failure to seek care and result in high mortality during hospitalization and during the post discharge period, a period of increasingly recognized vulnerability. The purpose of this study is to explore the out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, as nearly one in five post-discharge deaths occurred while en route to a health facility, caregivers may not recognise symptoms early enough. Barriers to seeking healthcare for young children in sub-Saharan Africa include suboptimal access, high costs for families, and negative previous experiences with healthcare facilities 74 75. These may be exacerbated following a costly hospital admission for a family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as nearly one in five post-discharge deaths occurred while en route to a health facility, caregivers may not recognise symptoms early enough. Barriers to seeking healthcare for young children in sub-Saharan Africa include suboptimal access, high costs for families, and negative previous experiences with healthcare facilities 74 75. These may be exacerbated following a costly hospital admission for a family.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to seeking healthcare for young children in sub-Saharan Africa include suboptimal access, high costs for families, and negative previous experiences with healthcare facilities. 74 75 These may be exacerbated following a costly hospital admission for a family. Further studies assessing caregiver education regarding warning signs and symptoms that should prompt further clinical care following hospitalisation, and healthcare seeking behaviours following hospital discharge, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that out-of-pocket costs incurred during both admission and discharge, such as buying basic necessities (food, airtime, transportation, etc.) were financially burdensome to caregivers, and adversely affected the overall well-being of families [ 4 , 12 ]. In the absence of a national health insurance program [ 26 ], these and other treatment related costs can push households into poverty and discourage return for future care.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare services are free of charge at government owned health facilities and vary in premium fees at private-not-for-profit (PNFP) health facilities; however, patients incur substantial economic burden in accessing care regardless of facility ownership. A 2021 mixed methods study on out-of-pocket pediatric patient costs in Uganda found that total hospitalization costs, excluding missed wages, ranged from 62.1 USD among public sector regional referral hospitals to 124.5 USD among PNFP hospitals [ 12 ]. Such healthcare costs can significantly impact Ugandan families as approximately 42% of the population lives on less than $2.15 USD per day [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these analyses focus on the perspective of the healthcare system [ 13 , 22 , 23 ], but do not consider out-of-pocket costs and productivity losses. In LMICs such as Uganda that are yet to implement universal health coverage (UHC), where patients may incur out-of-pocket costs near or exceeding that of monthly earnings [ 24 ], inclusion of the societal perspective is important to explore the economic impact of healthcare interventions on patients. Lastly, no LMIC analysis has utilized economic modelling techniques to incorporate healthcare utilization costs and link intermediate outcomes to clinical endpoints.…”
Section: Introductionmentioning
confidence: 99%